Mixed versus impulse-oriented domain decomposition method for granular dynamics - Iceta, Damien; Dureisseix, David; Alart, Pierre (European Journal of Computational Mechanics, 2009)
In this article, we are concerned with the numerical simulation of granular media, characterized as a large scale discrete system, involving non smooth interactions. For such problems, domain decomposition approaches are potential interesting alternative solvers. Herein, two robust and generic monoscale approaches are formulated and compared. The first numerical results reveal a non standard behavior in term of numerical scalability.